The ISWI ATPase Smarca5 (Snf2h) Is Required for Proliferation and Differentiation of Hematopoietic Stem and Progenitor Cells. (15th April 2017) - Kokavec, Juraj; Zikmund, Tomas; Savvulidi, Filipp; Kulvait, Vojtech; Edelmann, Winfried; Skoultchi, Arthur I.; Stopka, Tomas
Abstract : The imitation switch nuclear ATPase Smarca5 (Snf2h) is one of the most conserved chromatin remodeling factors. It exists in a variety of oligosubunit complexes that move DNA with respect to the histone octamer to generate regularly spaced nucleosomal arrays. Smarca5 interacts with different accessory proteins and represents a molecular motor for DNA replication, repair, and transcription. We deleted Smarca5 at the onset of definitive hematopoiesis ( Vav1‐iCre ) and observed that animals die during late fetal development due to anemia. Hematopoietic stem and progenitor cells accumulated but their maturation toward erythroid and myeloid lineages was inhibited. Proerythroblasts were dysplastic while basophilic erythroblasts were blocked in G2/M and depleted. Smarca5 deficiency led to increased p53 levels, its activation at two residues, one associated with DNA damage (S15 Ph ° s ) second with CBP/p300 (K376 Ac ), and finally activation of the p53 targets. We also deleted Smarca5 in committed erythroid cells ( Epor‐iCre ) and observed that animals were anemic postnatally. Furthermore, 4‐hydroxytamoxifen‐mediated deletion of Smarca5 in the ex vivo cultures confirmed its requirement for erythroid cell proliferation. Thus, Smarca5 plays indispensable roles during early hematopoiesis and erythropoiesis. Stem Cells 2017;35:1614–1623 Abstract : Smarca5 requirement during mouse hematopoietic development . Hematopoietic stem cells (HSCs) lacking Smarca5 temporarily activate proliferation followed by G2/M arrest during erythroid and myeloid differentiation leading to fatal anemia with tetraploid erythroblasts and p53 activation. Erythroid‐specific deletion of Smarca5 resulted in milder phenotypes: anemia and tetraploidy.